Effects of Freezing Lycorma delicatula Egg Masses on Nymph Emergence and Parasitization by Anastatus orientalis - Gómez-Marco, Francesc; Hoddle, Mark S. (Frontiers in Insect Science, 2022)
Lycorma delicatula (White) (Hemiptera: Fulgoridae), native to China, was first detected in Pennsylvania, U.S. in 2014. This polyphagous pest can feed on over 70 plant species including agricultural crops, like grapes, that have high economic value. Anastatus orientalis Yang and Choi (Hymenoptera: Eupelmidae) is an egg parasitoid associated with L. delicatula egg masses in China that is being evaluated for possible introduction into the U.S. for classical biological control of L. delicatula. In support of this program, the suitability of frozen L. delicatula eggs for parasitization by A. orientalis was evaluated in a quarantine laboratory. Host egg masses held for four different cold storage periods (5°C for <1, 4, 8 and 11 months) were frozen at -40°C for 1 hour or 24 hours and exposed to female A. orientalis for parasitization for seven days. Following this experimental exposure period, rates of L. delicatula nymph emergence and A. orientalis parasitism were assessed for each of the eight different cold storage treatments. Host acceptance and suitability of frozen L. delicatula eggs by A. orientalis was assessed in terms of percentage parasitism, offspring sex ratio, and hind tibia length of emerged parasitoids. Results indicated that L. delicatula nymphs failed to emerge from eggs that were exposed to -40°C for 1 hour and 24 hours and A. orientalis could successfully parasitize L. delicatula eggs regardless of cold storage and freezing treatment. These results add a new tool for long term maintenance of L. delicatula egg masses and rearing methods for egg parasitoids of this pest. Additionally, it may be possible to field deploy sentinel eggs of L. delicatula frozen at -40oC to survey for resident natural enemy species capable of parasitizing eggs of this pest in advance of anticipated L. delicatula invasions into new areas.